1998
DOI: 10.1038/3677
|View full text |Cite
|
Sign up to set email alerts
|

Development of the quantal properties of evoked and spontaneous synaptic currents at a brain synapse

Abstract: In many studies of central synaptic transmission, the quantal properties of miniature synaptic events do not match those derived from synaptic events evoked by action potentials. Here we show that at mossy fiber-granule cell (MF-gc) synapses of mature cerebellum, evoked excitatory postsynaptic currents (EPSCs) are multiquantal, and their amplitudes vary in discrete steps, whereas miniature (m)EPSCs are monoquantal or multiquantal with quantal parameters identical to those of the EPSCs. In contrast, at immature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 46 publications
6
85
4
Order By: Relevance
“…Second, it allowed us to use quantal analysis techniques. To be successful, quantal analysis requires low levels of quantal variance, and this is aided by the fact that quantal variance decreases with age (Wall and Usowicz, 1998). We also confirmed that the peaks we identified in our amplitude histograms did indeed correspond to monoquantal responses (supplemental Figs.…”
Section: Discussionsupporting
confidence: 69%
“…Second, it allowed us to use quantal analysis techniques. To be successful, quantal analysis requires low levels of quantal variance, and this is aided by the fact that quantal variance decreases with age (Wall and Usowicz, 1998). We also confirmed that the peaks we identified in our amplitude histograms did indeed correspond to monoquantal responses (supplemental Figs.…”
Section: Discussionsupporting
confidence: 69%
“…However, variations in quantal size represent a second major contributing factor (21). For instance, variability in EPSC size in hippocampal neurons is to a large degree due to variations in the glutamate concentration reached in the synaptic cleft (35), although quantal variance appears to undergo developmental down-regulation at some CNS synapses (36). Even though several factors, such as the site of release, may play a role in such effects, the present study shows that vesicular content at glutamatergic synapses is variable and therefore a potential control point in presynaptic plasticity.…”
Section: Discussionmentioning
confidence: 76%
“…At vertebrate neuromuscular junctions, the quantum may be equated with spontaneous signals obtained in the absence of presynaptic action potentials, called miniature currents (or potentials) and believed to be due to release of one neurotransmitter vesicle. For central synapses, this issue remains an open question, as large miniature currents are suggested to arise from the concerted release of several presynaptic vesicles and to be the sum of several quanta [2][3][4][5] . Such multivesicular miniature events could reflect tetrodotoxinresistant action potentials in presynaptic terminals 6 .…”
mentioning
confidence: 99%